Sexual Orientation and Earnings: New Evidence from the United Kingdom. (January 2018) - Aksoy, Cevat G.; Carpenter, Christopher S.; Frank, Jeff
Most prior work on sexual orientation and labor market earnings has relied either on individual-level surveys with small samples of sexual minorities or on large samples of same-sex couples. For this study, the authors use a large individual-level data set from the United Kingdom that allows investigation of both constructs. They replicate the well-documented lesbian advantage and gay male penalty in couples-based comparisons but show that these effects are absent in similarly specified models of non-partnered workers. This finding suggests that couples-based samples overstate the true earnings differences attributable to a minority sexual orientation as well as that household specialization plays an important role in the lesbian earnings advantage. Results also show that no significant lesbian advantage or gay male penalty is observed in London. Finally, they find robust evidence that bisexual men earn significantly less than otherwise similar heterosexual men. The authors discuss how the effects reconcile with theories of specialization and discrimination.